MASTERY OF PATIENT MEDICAL RECORD ACCESS AS EVIDENCE TOOL MEDICAL DISPUTE CASES IN PERSPECTIVE FAIR AND TRANSPARENT LAW ENFORCEMENT - Lamo Hot Tagam Sormin; Aloysius Agung Widi Wandono; Prasetyo (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
Medical records are documents containing patient identity data, examinations, treatments, actions, and other services that have been provided to patients that are made using an electronic system intended for organizing medical records. Related to medical records is the confidentiality of health documents that contain the patient's personal health secrets. Medical records are currently one of the five pieces of evidence that determine the resolution of medical disputes. The problem that arises is what is the legal position of patient medical record evidence in proving medical dispute cases in court? and how can legal justice be upheld in relation to restrictions on access to control of patient medical records by hospitals? This research is basically a normative legal research, namely a scientific approach that uses written legal materials as the main source in analyzing legal problems, and enforcing legal norms. The conclusion is that medical records must be made in electronic form or using digital means. That in the implementation of medical services can also be done in two ways, namely through conventional medical service facilities such as in health facilities and medical services carried out digitally, namely telemedicine. Thus, the position of medical records as evidence in medical disputes is very important, especially in realizing transparent justice both at the MDP level and in court. Medical records, both electronic and non-electronic, have an important position as evidence in medical disputes. The presence of transparent medical records is very important in realizing justice, both at the Professional Disciplinary Enforcement Council (MDP) level and in court.